Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students’ Speaking Skill in Online EFL Speaking Course Through Students’ Self-made YouTube videos

Abstract: In online EFL speaking course, the teaching and learning activity in the classroom held through the Web 2.0 technologies. Since COVID-19 was announced as national pandemic, all the teaching and learning activities need to be held through online platforms. This also includes the task given to the students, and the assessment done by the teachers. Teachers need to assess students' speaking skill through online platform, namely YouTube. Students uploaded their self-recorded video (SRV) to YouTube, then the teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…According to research conducted by (Saed et al, 2021), "As English learning material, YouTube video improved students' speaking skills including content, fluency, grammar, pronunciation, and vocabulary." This is consistent with the results of the other study conducted by Balbay & Kilis (2017); Saud Albahlal (2019); Shofatunnisa et al, (2021);and Rusgandi, Ali Ashari (2019). Another study designed by Binmahboob (2020) delivered the study's findings, which showed that English teachers prove that YouTube is a highly advantageous instructional tool in developing secondary school students' speaking skills.…”
Section: Youtube For Developing Speaking Skillsupporting
confidence: 93%
See 1 more Smart Citation
“…According to research conducted by (Saed et al, 2021), "As English learning material, YouTube video improved students' speaking skills including content, fluency, grammar, pronunciation, and vocabulary." This is consistent with the results of the other study conducted by Balbay & Kilis (2017); Saud Albahlal (2019); Shofatunnisa et al, (2021);and Rusgandi, Ali Ashari (2019). Another study designed by Binmahboob (2020) delivered the study's findings, which showed that English teachers prove that YouTube is a highly advantageous instructional tool in developing secondary school students' speaking skills.…”
Section: Youtube For Developing Speaking Skillsupporting
confidence: 93%
“…Recent studies have focused on using YouTube as Digital Learning Media in ELT to enhance student's general learning skills, autonomous learning, self-motivation, and confidence (Yusri et al, 2018;Lestari et al, 2019;Putri, 2019;Maziriri et al, 2020;Wang et al, 2021) in some ways of implementation (Atmojo & Priyo, 2020;Amaliah, 2021;Bardakci, 2019;Murni, et al, 2021;Ariantini., et.al, 2021;Sakkir et al, 2020;Yusuf, 2020;Abbas, N., F.& Qassim, T., 2020;Srinivasacharlu, 2020;Saban, 2020;Nasution, 2019;Latifah, 2019). YouTube has been argued to enhance students' listening skills (Chien et al, 2020;Istifci & Dogan Ucar, 2021, Saputra, Y., & Fatimah, 2018, improve students' speaking skills (Shofatunnisa et al, 2021;Sari et al, 2020;Balbay & Kilis, 2017;Albahlal, 2019;Saed et al, 2021;Binmahboob, 2020;Rusgandi, Ali Ashari, 2019;Sari, 2018) while supporting their writing and reading skill (Olasina, 2017;Alobaid, 2020;Noortyani Rusma, 2019), in more bilingual learning (Poramathikul et al, 2020;Listiani et al, 2021) with more independent and self-regulated learning (Latifah, 2019). Several studies have been formulated to discuss the advantages of implementing YouTube to improve students' vocabulary, grammar, and pronunciation (Kabooha & Elyas, 2018;Sahayu, 2020;…”
Section: Introductionmentioning
confidence: 99%
“…This finding shows that students need to be evaluated and supported psychosocially in order to gain the competencies required by the midwifery profession. Shofatunnisa et al (2020) stated that students' use of videoassisted learning method improved their professional speaking skills such as pronunciation, posture, mimicry and facial expression (Shofatunnisa et al, 2021). In the present study, two of the students stated that they noticed their missing points after shooting a video of themselves, five of them had difficulty in speaking in front of the camera even though they knew the application, and three of them stated that it was difficult to shoot videos at home conditions because they were distracted quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observations from past studies, the results offered useful insights related to students' satisfaction levels in online speaking assessments. Shofatunnisa et al, (2021) in their study showed that students were highly satisfied with online speaking assessment because it provided them more flexibility and convenience in completing the tasks as well as to upload their responses anytime and from any location they preferred. By reviewing past studies such as Azmina (2017), Peimani & Kamalipour (2022), Baleni (2015) and Afacan Adanir et al, (2020), it shows that students' satisfaction is also included in perception of students towards online learning and assessment.…”
Section: Satisfactionmentioning
confidence: 99%
“…A study conducted by Nova (2022) stated that use of technology raises students' nervousness during speaking even though they are well-prepared because they are worried about technical problems that could happen like disruption in internet connection, limited quota, and ineffective earphones. Moreover, the advantages of technology reduce the purity of students' English-speaking skills as students are allowed to edit their videos on Canva software and YouTube appliances (Shofatunnisa et al 2021). Due to variations in findings, this research includes as a variable the perception of students on the use of technology in the execution of online assessment.…”
Section: Use Of Technologymentioning
confidence: 99%